Challenges and Solutions for Decision Making in the Era of Big Data - Alifia, Rivi Ananda; Safitri, Naila Rahma; Irhami, Dinda Martha; Hidayat N, Rusdi; Kusumasari, Indah Respati (Jurnal Bisnis dan Komunikasi Digital, 2025)
Big data has become a transformative force in the business world, revolutionizing how companies process information to make more accurate and data-driven strategic decisions. By leveraging the ability to integrate vast amounts of ever-growing data from various sources, businesses can now uncover hidden patterns that were previously difficult to detect, forecast market trends with higher precision, and enhance operational efficiency across all business lines. However, this immense potential can only be realized through a structured approach involving meticulous data management, the development of advanced analytical skills, and the adoption of cutting-edge technologies. This article explores the fundamental concepts of big data, strategies for its management, and practical applications in key sectors. Additionally, it delves into major challenges such as data privacy, infrastructure limitations, and technology integration, accompanied by case-based solutions to help companies maximize opportunities from the big data revolution.